Synergistic Effects of N-Acetylcysteine and Mesenchymal Stem Cell in a Lipopolysaccharide-Induced Interstitial Cystitis Rat Model - Jung Hyun Shin; Chae-Min Ryu; Hyein Ju; Hwan Yeul Yu; Sujin Song; Dong-Myung Shin; Myung-Soo Choo (Cells, 2019)
The purpose of this study was to reduce the amount of stem cells used in treating preclinical interstitial cystitis (IC model) by investigating the synergistic effects of multipotent mesenchymal stem cells (M-MSCs; human embryonic stem cell-derived) and N-acetylcysteine (NAC). Eight-week-old female Sprague-Dawley rats were divided into seven groups, i.e., sham (n = 10), lipopolysaccharide/protamine sulfate (LPS/PS; n = 10), LPS/PS + NAC (n = 10), LPS/PS with 25K MSC (n = 10), LPS/PS with 50K MSC (n = 10) LPS/PS + 25K MSC + NAC (n = 10), and LPS/PS + 50K MSC + NAC (n = 10). To induce the IC rat model, protamine sulfate (10 mg, 45 min) and LPS (750 μg, 30 min) were instilled once a week for five consecutive weeks via a transurethral PE-50 catheter. Phosphate-buffered saline (PBS) was used in the sham group. One week after the final instillation, M-MSCs with two suboptimal dosages (i.e., 2.5 or 5.0 × 104 cells) were directly transplanted into the outer-layer of the bladder. Simultaneously, 200 mg/kg of NAC or PBS was intraperitoneally injected daily for five days. The therapeutic outcome was evaluated one week after M-MSC or PBS injection by awake cystometry and histological analysis. Functionally, LPS/PS insult led to irregular micturition, decreased intercontraction intervals, and decreased micturition volume. Both monotherapy and combination therapy significantly increased contraction intervals, increased urination volume, and reduced the residual volume, thereby improving the urination parameters compared to those of the LPS group. In particular, a combination of NAC dramatically reduced the amount of M-MSCs used for significant restoration in histological damage, including inflammation and apoptosis. Both M-MSCs and NAC-based therapy had a beneficial effect on improving voiding dysfunction, regenerating denudated urothelium, and relieving tissue inflammation in the LPS-induced IC/BPS rat model. The combination of M-MSC and NAC was superior to MSC or NAC monotherapy, with therapeutic efficacy that was comparable to that of previously optimized cell dosage (1000K) without compromised therapeutic efficacy.